Utilization, financial outcomes and stakeholder perspectives of a re-organized adult sickle cell program - Rousseau, Robert; Weisberg, Daniel F.; Gorero, Jack; Parwani, Vivek; Bozzo, Janis; Kenyon, Kathleen; Smith, Constance; Cole, Joanna; Curtis, Susanna; Forray, Ariadna; Roberts, John D. (PLOS ONE, 2020)
In 2011 Yale New Haven Hospital, in response to high utilization of acute care services and widespread patient and health care personnel dissatisfaction, set out to improve its care of adults living with sickle cell disease. Re-organization components included recruitment of additional personnel; re-locating inpatients to a single nursing unit; reducing the number of involved providers; personalized care plans for pain management; setting limits upon access to parenteral opioids; and an emphasis upon clinic visits focused upon home management of pain as well as specialty and primary care. Outcomes included dramatic reductions in inpatient days (79%), emergency department visits (63%), and hospitalizations (53%); an increase in outpatient visits (31%); and a decrease in costs (49%). Providers and nurses viewed the re-organization and outcomes positively. Most patients reported improvements in pain control and life style; many patients thought the re-organization process was unfair. Their primary complaint was a lack of shared decision-making. We attribute the contrast in these perspectives to the inherent difficulties of managing recurrent acute and chronic pain with opioids, especially within the context of the imbalance in wellness, power, and privilege between persons living with sickle cell disease, predominantly persons of color and poor socio-economic status, and health care organizations and their personnel.